Paragenetic specularite and adularia (Elba, Italy): concordant (U + Th)-He and K-Ar ages - Lippolt, Hans J.; Wernicke, Rolf Stephan; Bähr, Roland (Earth and planetary science letters, 1995)
In order to test the usefulness of the helium method for detecting young geological events in hematite, U, Th and4He concentrations were analyzed in five specularite samples from Rio Marina-type hematite deposits (northeastern Elba, Italy). Four specularite samples define a(U + 0.235Th)/4He isochron age of 5.39 ± 0.46 Ma (2σ). The isochron intercepts the4He axis at 49 ± 88 pl/g (2σ). Adularia, which is paragenetic with specularite in one sample used for the isochron, gives a meanK/Ar age of 5.32 ± 0.11 Ma. In addition, two specularite samples, one from Rio Marina and one from Terra Nera (southeastern Elba) give helium model ages of 6.4 ± 0.4 and 7.3 ± 0.4 Ma respectively. Depending on the model of genesis, the high ages reflect incomplete4He degassing and/or4Heexcess. The study demonstrates that geologically meaningful helium ages as young as Pliocene can be obtained from specularite in spite of expected interferences from initial helium. If the4He axis intercept is a general measure of initial4He in hematite its effect on the calculated ages in Mesozoic hematites in previous studies is negligible. The age concordance implies that similar concordance should exist in samples with a known thermal history much older than Pliocene. Moreover, the helium method could also work on specularite with a thermal history younger than Pliocene.
Elektronische Reproduktion der Druck-Ausgabe 16. Dezember 1999
Gesehen am 17.01.2023